Relationship of Socio-economic Profile of the Turmeric Growing Farmers to their Training Need - Anil Kumar , A.K. Paswan , M. N. Ansari and A. K.Singh, (Indian Journal of Extension Education, 2016)
A study on training needs of turmeric growers in Samastipur and Muzaffarpur district of Bihar was undertaken. Thefindings revealed that majority of turmeric growers belong to the advance age group, literate, possessing small size of landholding, low income group. The maximum per cent age of respondents has medium economic motivation, crop intensityand level of knowledge. The results revealed that training need in plant protection measure was given top priority. Theother important areas of cultivation in which turmeric growers have shown their desire were high yielding variety,fungicidal seed treatment, sowing method, sowing time and fertilizer management. The most important factorsinfluencing the training needs of turmeric growers in relation to turmeric production were cropping intensity, economicmotivation and knowledge which were found to be positively and significantly associated with the training need ofturmeric growers. These factors should be kept in view while formulating any training programme. The other independentvariables such as family education, size of land holding and area under turmeric cultivation were not able to create suchpositive correlation as in the case of other selected independent variables.